MULTI-ETHNICITY AND MULTICULTURALISM OF GLOBALIZATION EPOCH - Нельга, О. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The main thesis of an article is that ethnical history of mankind in the context of globalization can be directed towards multi-ethnicity but not towards multiculturalism. The phenomenon of common socio-cultural space that is being expanded due to globalization would play main role in this process, but the main condition is neutralization of the factor of immigrant`s diffusion in the borders of national European states.